2017
DOI: 10.5424/sjar/2017151-9288
|View full text |Cite
|
Sign up to set email alerts
|

Chitosans of different molecular weight enhance potato (Solanum tuberosum L.) yield in a field trial

Abstract: Physico-chemical features of chitosan affect its biological activity on plants. In this work, the influence of chitosan molecular mass in potato (Solanum tuberosum L.) yields was investigated. By using chitosan polymers of high (CH-1) and low (CH-2) molecular weight and a hydrolysed chitosan derivative (CHH), two experiments were performed under field conditions to determine the effect of these polymers on yields of two potato varieties, 'Call White' and 'Santana'. For this purpose, the foliar spray of low dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Although the use of chitosan sounds promising in improving plant performance, it highly depends on its concentration and time of application. Previous studies showed that lower concentrations of chitosan increase the productivity of potato and vice versa (Falcón-Rodríguez et al 2017). The same trend was reported by (Abdel-Mawgoud, 2010) in strawberries.…”
Section: Introductionsupporting
confidence: 81%
“…Although the use of chitosan sounds promising in improving plant performance, it highly depends on its concentration and time of application. Previous studies showed that lower concentrations of chitosan increase the productivity of potato and vice versa (Falcón-Rodríguez et al 2017). The same trend was reported by (Abdel-Mawgoud, 2010) in strawberries.…”
Section: Introductionsupporting
confidence: 81%
“…As this protein expression was observed 24 h after chitosan treatment, these findings are in agreement with our observations of an upregulation of the corresponding genes in the first hours after chitosan treatment. Additionally, field trials with chitosan-treated potato plants resulted in up to 30% enhanced potato yields ( Falcón-Rodríguez et al., 2017 ). Equally, foliar application of chitosan enhanced both growth and drought tolerance of potato plants ( Muley et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo [60] Increased plant growth and yield In vitro and in vivo [61] Tomato (Solanum lycopersicum)…”
Section: Increased Of Tuber Sizementioning
confidence: 99%